Antifungal activity of potassium silicate to control crown rot in banana (Bioagro, 2025)
Crown rot is the most important postharvest disease in banana worldwide. The post-harvest antifungal activity of potassium silicate (SP) against crown rot (CR) of banana inoculated with Colletotrichum musae (Cm) was determined. Treatments with SP (from 30 to 160 mM) were tested through in vitro and in vivo (from 70 to 300 mM) experiments. The 90 mM concentration of SP in in vivo experiments was selected as the most effective and used in experiments on the influence of dip temperature on PS effectiveness. Curative dip treatments of 90 mM SP at 40 °C for 20 min applied alone or in combination with low doses of thiabendazole (TBZ) were evaluated on CR, as well as the effect of SP on banana quality. SP at 90 mM totally inhibited the mycelial growth of Cm as well as significantly reduced the severity of CR in both preventive (51.1 %) and curative (59,5%) treatments in in vivo primary experiments. Among the dips with PS at 90 mM for 20 min tested at different temperatures, the dip at 40 °C was selected as the most effective. The combined curative dip treatment, SP+TBZ, improved the control against CR with an incidence reduction of 91.6 %. SP does not affect banana fruit quality.
Keywords: Colletotrichum musae; incidence; mycelium; quality; severity